Extreme right images of radical authenticity: Multimodal aesthetics of history, nature, and gender roles in social media. Issue 3 (3rd July 2017) - Forchtner, Bernhard; Kølvraa, Christoffer
ABSTRACT: Over recent years, the German extreme right has undergone significant changes, including the appropriation of symbols, styles, and action repertoires of contemporary (youth) cultures, sometimes even taken from the far left. In this article, we investigate extreme right visual communication through Facebook, focusing on claims to truth and authentic Nazism in relation to 'history', 'nature', and 'gender roles'. These themes were central in National Socialism, but today need to be (re)negotiated vis-à-vis contemporary (youth) cultures. We show that while a traditional notion of ideological authority is enabled through visuals, there is also a strand of imagery depicting and celebrating 'intimate' communion. While this simultaneity leads to tensions within the 'ideal extreme right subject', we argue that such dilemmas can also be productive, allowing for the (re)negotiation of classic National Socialist doctrine in the context of contemporary (youth) cultures, and thus, potentially, for a revitalisation of the extreme right.